Postoperative Adjuvant Chemotherapy Improved the Prognosis in Locally Advanced Cervical Cancer Patients With Optimal Response to Neoadjuvant Chemotherapy - Feng, Xiaojie; Chen, Hongmin; Li, Lei; Gao, Ling; Wang, Li; Bai, Xupeng (Frontiers in Oncology, 2020)
Background. Few studies investigated the effectiveness of adjuvant chemotherapy (CT) in patients with optimal response to neoadjuvant CT (NACT), and an optimal number of treatment cycles for these patients remains unknown. Methods. A total of 261 Chinese patients with FIGO stage Ib2–IIb cervical cancer who showed an optimal response to NACT were included after radical surgery (RS), and the disease-free survival (DFS) and overall survival (OS) of patients treated with different cycles of postoperative adjuvant CT were compared. Results. We found that patients treated with different cycles of postoperative adjuvant CT were significantly better than those without further therapy. The multivariate analysis showed that postoperative adjuvant CT was an independent prognostic factor for DFS. However, there was no significant difference in the DFS and OS between patients who had 3 cycles of adjuvant CT and those with 6 cycles. Further analysis revealed a significant association of 6 cycles of adjuvant CT with increased risk of leukopenia, nausea/vomiting, and rash. Conclusion. These data suggest that additional 3 cycles of adjuvant CT after NACT + RS may improve the clinical outcome of optimal responders in terms of DFS, OS, and drug toxicity.